Contested extractivism, society and the state: struggles over mining and mand - Engels, Bettina; Dietz, Kristina (Development, Justice and Citizenship, 2017)
This book empirically discusses recent struggles over land and mining, exploring state-society relations conflicts on various scales. In contrast with the existing literature, analyses in this volume deliberately focus on large-scale land use changes both in relation to the expansion of industrial mining and to agro-industry. The authors contend that there are significant parallels between contestations over different variants of resource extractivism, as they reflect the same global trends and processes. Chapters draw on critical theoretical approaches from political ecology, political economy, spatial theory, contentious politics, and the study of democracy. The authors not only provide empirical insights on actual resource struggles from different world regions based on in-depth field research, but also contribute to theory-building by linking concepts from various critical approaches to one another, developing a perspective for analysing struggles over resources related to current global crisis phenomena